2012
DOI: 10.1590/s0365-05962012000500001
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha and the cytokine network in psoriasis

Abstract: New molecular methods of research have greatly expanded the knowledge about the role of cytokines in several diseases, including psoriasis. The work orchestrated by these peptides is essential for the communication between resident inflammatory cells (keratinocytes and endothelial cells) and infiltrating cells (neutrophils, lymphocytes, Langerhans cells). This is a complex network due to redundancy, synergism and, sometimes, the antagonism of cytokines, which prevents full understanding of the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 55 publications
1
40
0
3
Order By: Relevance
“…Serwin et al [40] found that serum TNFR-1 levels were significantly increased in patients with psoriasis compared with those in controls. Brotas et al [41] reported that TNF- α has various effects on the cellular level in psoriasis. Coimbra et al [42] found no differences in TNF levels between patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Serwin et al [40] found that serum TNFR-1 levels were significantly increased in patients with psoriasis compared with those in controls. Brotas et al [41] reported that TNF- α has various effects on the cellular level in psoriasis. Coimbra et al [42] found no differences in TNF levels between patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with the extensive cross-talk between keratinocytes and immune cells in psoriasis, it is unclear which is the major source of these cytokines, and the role of activated keratinocytes in cytokine production cannot be excluded. In fact, keratinocytes are thought to be the primary producers of IL-1 in the skin (Brotas et al, 2012). To stimulate cytokine production by keratinocytes, we used TPA, which is a known inducer of the keratinocyte inflammatory response (Kim et al, 2014).…”
Section: Mmf-induced Effects In Keratinocytesmentioning
confidence: 99%
“…TNF-α is secreted by a variety of cells such as macrophages, monocytes, neutrophils, T cells, natural killer cells, adipocytes, and fibroblasts (Fahey et al, 1995; Jovinge et al, 1996; Cawthorn and Sethi, 2008; Ambler et al, 2012; Brotas et al, 2012; Zakka et al, 2012), and its signaling is transduced through TNF receptor 1 (TNFR1) and TNF receptor 2 (TNFR2). Soluble TNF-α binds preferentially to TNFR1, which is expressed in neurons (Brambilla et al, 2011) whereas transmembrane TNF-α binds to TNFR2, which is mainly expressed in immune cells such as those of the myeloid lineage, lymphocytes, and macrophages (McCoy and Tansey, 2008).…”
Section: Tumor Necrosis Factor-αmentioning
confidence: 99%